2008
DOI: 10.1093/annonc/mdn363
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the safety and pharmacokinetics of trabectedin in combination with pegylated liposomal doxorubicin in patients with advanced malignancies

Abstract: Trabectedin combined with PLD is generally well tolerated at therapeutic doses of both drugs in pretreated patients with diverse tumor types and appears to provide clinical benefit. These results support the need for additional studies of this combination in appropriate cancer types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
6
29
0
Order By: Relevance
“…PLD have been extensively employed in some non-hematological neoplasm as breast cancer, with similar results in CR rate and OS to conventional doxorubicin [11,15] . But, most of these studies did not have a longer follow-up and only analyzed the presence of acute cardiac toxicity around the treatment and for < 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLD have been extensively employed in some non-hematological neoplasm as breast cancer, with similar results in CR rate and OS to conventional doxorubicin [11,15] . But, most of these studies did not have a longer follow-up and only analyzed the presence of acute cardiac toxicity around the treatment and for < 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of liposomal and pegylated liposomal anthracyclines open a new options in treatment of this setting of patients because these drugs showed similar antitumoral activity and reduced cardiac toxicity [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Trabectedin is demonstrated to be active in breast, ovarian, nonsmall cell lung cancers, melanoma and sarcoma and several reports showed that it could be safely combined with other agents such as gemcitabine and PLD [72][73][74]. Monk reported a phase III study on recurrent, partially platinum-sensitive OCs treated with trabectedin plus PLD.…”
Section: Beyond Platinum-based Chemotherapy: Towards a Personalized Tmentioning
confidence: 99%
“…Several Phase I trials of trabectedin-based combinations have been reported, and showed that trabectedin could be safely combined with doxorubicin, 27,28 PLD, 29 gemcitabine, 30 taxanes, 31,32 and capecitabine. 33 A recently published article has reported on a Phase I trial investigating the combination of trabectedin and cisplatin.…”
Section: Trabectedin-based Combinationsmentioning
confidence: 99%
“…29 Thirty-six patients with normal liver function, prior doxorubicin exposure , 250 mg/m², and normal cardiac function were enrolled. A broad range of advanced malignancies was represented, the most common being sarcoma (n = 16), ovarian cancer (n = 4), and pancreatic cancer (n = 2).…”
mentioning
confidence: 99%